KEDUDUKAN HUKUM PEMEGANG SAHAM YANG TIDAK MENYETOR PENUH MODAL YANG DITEMPATKAN DALAM PERSEROAN - AZHAR AZHAR (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Bismar2. Mahmul Siregar3. T. Keizerina Devi A A limited liability company is established according to an “agreement”; it is a capital association among the founders and/or share-holders, and it has to fulfill the requirements in a contract law. The research uses juridical normative method which analyzes the prevailing legal. The nature of the research was descriptive analytic. The research uses juridical normative method which analyzes the prevailing legal provisions such as Law No. 40/2007 on Limited Liability Company and PP (Government Regulation) No. 29/2016 on the Amendment of Initial Capital of the Limited Liability Company. The result of the research shows that a shareholder who does not deposit full initial capital is considered legally defective and does not have any legality and validity as a shareholder. He has no right of the company’s dividend and is categorized as having done a default against the contract of establishing a Limited Liability Company and an illegal act against the legal provisions concerning a limited liability company and against Article 33 of Law No 40/2007 on Limited Liability Company in particular.Keywords: Shareholder, Not Deposit Initial Capital, Default/Illegal Act